A influência das variáveis de entorno e do edifício sobre as iluminâncias e o ofuscamento nos ambientes internos: um estudo de caso em edifícios residenciais multipavimentos em recorte urbano na cidade de João Pessoa-PB - Leal, Lilianne de Queiroz (2013)
Due to the densification of urban centers and the verticalization, the urban grid has been modified to the point of significantly affecting the availability of daylight in buildings. Under this view, the scope of this paper discusses the influence of variables around and of the building on the illuminance and glare of its indoor environments. From a case study in Manaíra, a district in the city of João Pessoa PB, the aspects which were evaluated as independent variables were: the degree of obstruction of the surroundings, the properties of the external vertical surfaces - reflectance and solar protection elements, the height of the floor and orientation. The dependent variables related to daylighting in indoor environments were: the illuminance distribution, the percentage of the illuminated area inserted into the useful range of illuminance and the occurrence of glare. Through computer simulation, by using the Daysim software, the use of dynamic metric allowed the extraction of data of the Useful Daylight Illuminance (UDI 300-3000lux), besides values in temporal and spatial scale in the period of a year corresponding to the weather file of the city mentioned. In addition, the ratios of Daylight Glare Probability (DGP) were found through the Evalglare program. It was possible, by the use of graphic and statistical methods, to find differences between the 120 models of indoor environments inserted in three different urban settings and to compare the research variables which showed the strongest influence. It was noticed that the sun protection devices in facades contributed most significantly to the useful frequency range of illuminance compared to scenarios without shading, being it paramount to the increase of lighting levels and the reduction of visual discomfort. Additionally, it was noticed that the most clogged pavements, like the ground, were the most uniform. However, there was a level of illuminance below the range of sufficiency (UDI <3000lux). Regarding the variables of the building, the facades which are oriented Northwest and Northeast have better performance, featuring environments with minor variations of illuminance, satisfactory percentage of illuminated area above 75% of UDI, as well as larger bands of unnoticeable glare. Differently, the Southwest facade recorded the worst results in respect of lighting levels and the Southeast facade is the most prone to the increase of glare probability, especially in embedded environments of scenarios with maximum reflection of the facades and in situations without interference from the surroundings and with the contribution of direct light.